Interaction Between Malat1 and miR-499-5p Regulates Meis1 Expression and Function with a Net Impact on Cell Proliferation - Salma A. Fahim; Manon Ragheb; Ibrahim Hassan Fayed; Aya Osama; Ahmed Karam; Sameh Magdeldin; Rana Metwale; Mohamed Dief Allah Abdalmoneam Elsayed; Ahmed Abdellatif; Hesham A. Sadek; Shereen Ahmed El Sobky; Nada El-Ekiaby; et al. (Cells)
Meis1 is a transcription factor involved in numerous functions including development and proliferation and has been previously shown to harness cell cycle progression. In this study, we used in silico analysis to predict that miR-499-5p targets Meis1 and that Malat1 sponges miR-499-5p. For the first time, we demonstrated that the overexpression of miR-499-5p led to the downregulation of Meis1 mRNA and protein in C166 cells by directly binding to its 3’UTR. Moreover, knocking down Malat1 increased miR-499-5p expression, subsequently suppressing Meis1. Through BrdU incorporation assay, we showed that the knockdown of Malat1, Meis1, or mimicking with miR-499-5p promoted cell proliferation. Enrichment analyses on proteins identified via mass spectrometry after manipulating Malat1, miR-499-5p, or Meis1 revealed a multitude of differentially expressed proteins related to cell cycle, cell division, and key pathways like Wnt and mTOR, essential for cell proliferation. Collectively, our findings confirm that Malat1 sponges miR-499-5p, regulating Meis1, and that Malat1/miR-499-5p/Meis1 could potentially form an axis that has a pivotal influence on cellular proliferation.